Effect of Animated Video Based Digital Education on Anemia Knowledge among Adolescent Girls: A Pre Post Study - Astri Sapariah; Hafizah Che Hassan; Fatimah Yahya (TIN: Terapan Informatika Nusantara, 2026)
Anemia remains a major public health problem among adolescent girls, particularly in developing countries, where inadequate iron intake, menstrual blood loss, and limited health literacy contribute to its high prevalence. Insufficient knowledge regarding the causes, symptoms, and prevention of anemia often leads to poor dietary practices and low adherence to iron supplementation programs. In response to these challenges, digital health education using animated video media has emerged as an innovative and engaging strategy for improving adolescents’ understanding of health-related issues. This study aimed to examine the effect of animated video–based digital education on anemia-related knowledge among adolescent girls in a senior high school setting. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted involving 52 adolescent girls selected through purposive sampling at SMAN 1 Cisarua, Indonesia. Participants received an educational intervention in the form of an animated video addressing the definition, causes, symptoms, consequences, and prevention of anemia. Knowledge levels were measured before and after the intervention using a validated structured questionnaire. Data were analyzed using a paired sample t-test after confirming normal data distribution. The results demonstrated a statistically significant increase in mean knowledge scores following the intervention (p < 0.001), indicating a meaningful improvement in participants’ understanding of anemia. These findings suggest that animated video–based digital education is an effective and accessible approach to enhancing anemia-related knowledge among adolescent girls. The use of such media may support school-based health education programs and contribute to strengthening anemia prevention efforts in adolescent populations.